A New Hilbert-type integral inequality with a non-homogeneous kernel and its extension - Wu, Weiliang (Global Journal of Mathematical Analysis, 2016)
By introducing some parameters , using the weight function and the technique of real analysis, a new Â Hilbert-type integral inequality with a non-homogeneous kernel as \(1|1-axy|^λ_2 (a≥1)\) and its equivalent form are established. As application, the constant factor on the plane is the best value and its extension form with some parameters is also considered.